Analysis of Production Cost Calculations using the Direct Costing Method at PT Fortuna Inti Alam - Priskila Manuho; David Paul Elia Saerang; Rudy Johanis Pusung (Formosa Journal of Applied Sciences, 2023)
The Direct Costing method is a production cost calculation method that only charges costs that are variable or that are directly related to the product. This research aims to find out how to calculate production costs using the direct costing method at PT Fortuna Inti Alam. The research method used in this research is descriptive qualitative. The results of the research show that the calculation of production costs at PT Fortuna Inti Alam uses a company method that charges all costs incurred within the company, resulting in a total production cost of IDR 2,442,117,500. Meanwhile, using the direct costing method results in total production costs of IDR 2,075,470,000. The results of these calculations cause a difference in total production costs, namely Rp. 366,647,500, where calculating production costs using the direct costing method results in total production costs that are smaller than the company's method.